Hyperthyroidism in non-seminomatous testicular germ cell tumors: two case reports and literature review - Favero, Diletta; Oing, Christoph; Seidel, Christoph; Rescigno, Pasquale; Catalano, Fabio; Cremante, Malvina; Rebuzzi, Sara Elena; Gatto, Federico; Rosti, Giovanni; Ferone, Diego; Fornarini, Giuseppe; Cocchiara, Francesco (Frontiers in Oncology, 2024)
Background Human chorionic gonadotropin (hCG)–induced hyperthyroidism is a rare paraneoplastic syndrome observed in non-seminomatous testicular germ cell tumors, due to a cross-reaction between the β-subunit of hCG with the thyroid-stimulating hormone receptor. The precise prevalence of this paraneoplastic phenomenon is unclear as, in the majority of cases, hyperthyroidism remains subclinical. Case presentation Here, we present two cases of advanced metastatic non-seminomatous testicular germ cell tumors where patients exhibited signs and symptoms of thyrotoxicosis at primary diagnosis due to excessive serum β-hCG elevation, with complete remission of symptomatology after the start of oncological treatments and no signs of relapse at the time of publication of this report. Additionally, we provide a comprehensive review of the existing literature concerning this uncommon occurrence. Conclusion Despite being a rare event, the presence of hyperthyroidism or thyrotoxicosis without clear etiology in a young man should lead to consider less frequent causes such as testicular tumors. Even if patients typically have mild symptoms that resolve after chemotherapy, in rare cases, it can be a life-threatening condition that requires prompt recognition and specific intervention.